The Rosetta Stone project: III. ALMA synthetic observations of fragmentation in high-mass star-forming clumps - Nucara, Alice; Traficante, Alessio; Lebreuilly, Ugo; Tung, Ngo-Duy; Molinari, Sergio; Hennebelle, Patrick; Testi, Leonardo; Klessen, Ralf S.; Pelkonen, Veli-Matti; Avison, Adam; Benedettini, Milena; Coletta, Alessandro; et al. (Astronomy and astrophysics, 2025)
Context: The physical mechanisms that regulate the collapse of high-mass parsec-scale clumps and allow them to form clusters of new stars, including high-mass stars, represent a crucial aspect of star formation. Aims: To investigate these mechanisms, we developed the Rosetta Stone project: an end-to-end (simulations ⇔ observations) framework that is based on the systematic production of realistic synthetic observations of clump fragmentation and their subsequent comparison with real data. Methods: In this work, we compare ALMA 1.3 mm continuum dust emission observations from the Star formation in QUiescent And Luminous Objects (SQUALO) survey with a new set of 24 radiative magnetohydrodynamical (RMHD) simulations of high-mass clump fragmentation, post-processed using the CASA software to mimic the observing strategy of SQUALO (combining ACA and 12 m array). The simulations were initialized combining typical values of clump mass (500 and 1000 M⊙) and radius (∼0.4 pc) with two levels of turbulence (Mach number, M, of 7 and 10) and three levels of magnetization (normalized mass-to-magnetic-flux ratio, µ, of ∼3, 10, and 100). Following the clump evolution over time with two initial random seeds projected along three orthogonal directions, we produced a collection of 732 synthetic fields. On each field, we performed source extraction and photometry using the Hyper software, as in the SQUALO project, to quantitatively characterize how the initial conditions of the clump and the environment affect the observed fragmentation properties. Results: The synthetic observations of clump fragmentation at ∼7000 AU resolution revealed between 2 and 14 fragments per field, indicating a complex fragmentation process. Among the initial conditions of the simulations, magnetic fields have the largest impact on the fragment multiplicity at these scales. In advanced stages of clump evolution, a lower number of fragments is preferentially associated with magnetized clumps. The clump magnetization might also affect the clustering of fragments, favoring more tightly bound distributions when the magnetic field is stronger. Fragments identified at ∼7000 AU correspond to individual or multiple sink particles in ∼75% of the cases. This result suggests that not all identified fragments are actively forming stars. Both sink particles and fragments accrete mass throughout the whole clump evolution. This evidence favors a scenario in which fragments are not isolated from the environment and is thus consistent with results from the SQUALO survey. Conclusions: Our study demonstrates the importance of synthetic observations in interpreting results from interferometric observations.